Selenium-coated chitosan nanoparticles (CTS-Se NPs) improve grapevine (Vitis vinifera cv. Sultana) performance grown under lead (Pb) toxicity - Panahirad, Sima; Dadpour, Mohammadreza; Kulak, Muhittin; Vita, Federico; Gohari, Gholamreza; Fotopoulos, Vasileios (My University, 2025)
Selenium-coated chitosan nanoparticles (CTS-Se NPs) have been proposed as innovative engineered nanoparticles with the potential to alleviate various abiotic stresses, thereby enhancing plant growth and productivity. However, evidence of their efficacy remains limited. In this study, the effects of CTS-Se NPs (10 and 20 mg L⁻¹), along with CTS NPs (0.1%) and Se (20 mg L⁻¹), were evaluated for their potential to mitigate lead (Pb)-induced stress (0, 50, 100 mg kg⁻¹) on key agronomic and physio-biochemical traits of grapevine (Vitis vinifera L. cv. Sultana).
Keywords: Abiotic stress; Carrier; Coating; Nanotechnology